Sikap Guru Terhadap Penggunaan Internet Kajian Kes - Fathaiyah, Abdullah (1997)
Internet refers to the International Network of computer networks system. It is an important system for communication and information transfer. The aim of this research is to elucidate teachers’ attitudes towards the usage of Internet in schools. In this study, ‘attitude’ is referred to the teachers’ mental responses and perception towards the Internet. These responses would consequently effect teachers’ willingness and readiness to use the Internet in schools. Six teachers from four secondary schools in Wilayah Persekutuan who are Advisory Teachers of the Computer Clubs in their respective schools have been involved in this research. These 4 schools are the pioneer schools for the ‘Jaring Pendidikan Kebangsaan’ programme. These teachers were selected due to their keen interest and involvement in Internet activities of their schools. The teachers’ responses were measured through a questionaire adapted by a study carried out by Kang Wai Chin (1995). These responses can also measure the teachers’ readiness and willingness to use the Internet as a communicational tool and therefore increase their awareness towards the changes in the world of education. The result of this research proves that the teachers agree that Internet provides the best access in gaining the most current and up-to-date information. The outcome of this study also shows that the teachers are convinced and confident with their abilities in using the Internet in schools effectively.